UTHM Bargain: Marketplace App - Wan Mohd Lutpi, Wan Muhammad Aniq Irfan; Selamat, Norhanim (Applied Information Technology And Computer Science, 2025)
The widespread use of messaging platforms like WhatsApp and Telegram for buying and selling goods among UTHM community members has led to challenges such as inefficient item browsing and vulnerability to fraud due to the lack of proper verification. This project aims to develop UTHM Bargain, a dedicated mobile application for secure trading exclusively among UTHM members, verified through matriculation numbers. Developed using the prototype model, the project followed an object-oriented approach and applied user interface design principles with secure authentication mechanisms. The software used includes Flutter for mobile development and Firebase for backend services. Testing results showed the app successfully addressed the initial issues by offering an organized marketplace and robust user verification. Future enhancements may include integration of secure payment systems and expansion to other institutions.